Evidence for eomesodermin‐expressing innate‐like CD8+ KIR/NKG2A+ T cells in human adults and cord blood samples. Issue 7 (20th May 2015) - Jacomet, Florence; Cayssials, Emilie; Basbous, Sara; Levescot, Anaïs; Piccirilli, Nathalie; Desmier, Deborah; Robin, Aurélie; Barra, Anne; Giraud, Christine; Guilhot, François; Roy, Lydia; Herbelin, André; et al.
<x xml:space="preserve">Abstract</x> Polyclonal CD8+ T cells, with a marked innate/memory phenotype, high eomesodermin (Eomes) expression, and the capacity to generate IFN‐γ rapidly without prior exposure to antigen, have been described in mice. However, even though a pool of human CD8+ T cells expressing killer Ig‐like receptors (KIRs) was recently documented, the existence of a human equivalent of murine innate/memory CD8+ T cells remains to be established. Here, we provide evidence for a population of KIR/NKG2A+CD8+ T cells in healthy human adults sharing the same features, namely increased Eomes expression, prompt IFN‐γ production in response to innate‐like stimulation by IL‐12+IL‐18, and a potent antigen‐independent cytotoxic activity along with a preferential terminally differentiated effector memory phenotype. None of the above functional characteristics applied to the KIR/NKG2A− fraction of the Eomes+CD8+ T‐cell population, thereby underlining the ability of KIR/NKG2A to distinguish between "innate/memory‐like" and "conventional/memory" pools of CD8+ T cells. Remarkably, KIR/NKG2A+Eomes+CD8+ T cells with innate‐like functions and a memory/terminally differentiated effector memory phenotype were also identified in human cord blood, suggesting that their development did not depend on cognate antigens. Taken together, our results support the conclusion that CD8+ T cells co‐expressing Eomes and KIR/NKG2A may represent a new, functionally distinct "innate/memory‐like" subset in humans.